Not so gameful: A critical review of gamification in mobile energy applications. (May 2019) - Beck, Ariane L.; Chitalia, Sohum; Rai, Varun
Highlights: Review and analysis of use of gamification and behavioral constructs in energy apps. Energy apps that use more gamification components have higher user ratings. Energy apps are hard to find in online stores; designers should focus on search engine optimization. Apps should take a more intentional approach to gamified design and behavior theory. Sophisticated game design elements are not utilized and could improve user experience. Abstract: In order to help mitigate climate change and reduce the health-related consequences of air pollution, consumers need to be empowered to make better and more effective decisions regarding energy use. Utilities, government, and commercial entities offer numerous programs and consumer products to help individuals set or reach goals related to energy use. Many of these interventions and products have related apps that use gamification in some capacity in order to improve the user experience, offer motivation, and encourage behavior change. We identified 57 apps from nearly 2400 screened apps that both target direct energy use and employ at least one element of gamification. We evaluated these apps with specific focus on gamification components, game elements, and behavioral constructs. Our analysis shows that the average energy related app heavily underutilizes search engine optimization, gamification components, and game design elements, as well as the behavioral constructs known to impact energy-related decision-making and behavior. Our findings offer several insights for the design of more effective energy apps.